2022
DOI: 10.1093/g3journal/jkac277
|View full text |Cite
|
Sign up to set email alerts
|

Genome report: chromosome-level draft assemblies of the snow leopard, African leopard, and tiger (Panthera uncia, Panthera pardus pardus, and Panthera tigris)

Abstract: The big cats (genus Panthera) represent some of the most popular and charismatic species on the planet. Although some reference genomes are available for this clade, few are at the chromosome level, inhibiting high-resolution genomic studies. We assembled genomes from three members of the genus, the tiger (Panthera tigris), the snow leopard (Panthera uncia), and the African leopard (Panthera pardus pardus), at chromosome or near-chromosome level. We used a combination of short- and long-read technologies, as w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Lion trios were mapped to the original PanLeo1.0 assembly (Armstrong et al 2020) and the ‘mappable’ novel lion genome reported here (defined as the assembly’s haplotype 2 including X chromosome with the Y chromosome added). Tiger trios were mapped to the GenTig1.0 (Armstrong et al 2022) and PanTigT.MC.v3 (GCA_021130815.1; Shukla et al 2022) genomes. Clouded leopards were mapped to three genome assemblies: a short-read assembly (SaMing-1434 [GCA_027422525.1; Bursell et al 2022]) and two long-read assemblies (SNNU_Nneo_1 [GCA_030324275.1; Yuan et al 2023] and the primary haplotype assembly of mNeoNeb1 [GCA_028018385.1; Vertebrate Genomes Project 2023]).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lion trios were mapped to the original PanLeo1.0 assembly (Armstrong et al 2020) and the ‘mappable’ novel lion genome reported here (defined as the assembly’s haplotype 2 including X chromosome with the Y chromosome added). Tiger trios were mapped to the GenTig1.0 (Armstrong et al 2022) and PanTigT.MC.v3 (GCA_021130815.1; Shukla et al 2022) genomes. Clouded leopards were mapped to three genome assemblies: a short-read assembly (SaMing-1434 [GCA_027422525.1; Bursell et al 2022]) and two long-read assemblies (SNNU_Nneo_1 [GCA_030324275.1; Yuan et al 2023] and the primary haplotype assembly of mNeoNeb1 [GCA_028018385.1; Vertebrate Genomes Project 2023]).…”
Section: Methodsmentioning
confidence: 99%
“…Clouded leopards were mapped to three genome assemblies: a short-read assembly (SaMing-1434 [GCA_027422525.1; Bursell et al 2022]) and two long-read assemblies (SNNU_Nneo_1 [GCA_030324275.1; Yuan et al 2023] and the primary haplotype assembly of mNeoNeb1 [GCA_028018385.1; Vertebrate Genomes Project 2023]). Leopard, snow leopard, and jaguar data were mapped to the most contiguous reference genome available for each respective species (leopard: Ppardus1 [GCA_024362965.1; Armstrong et al 2022]; snow leopard: PanUnc1.0 [GCF_023721935.1; Armstrong et al 2022]; jaguar: Panthera_onca_HiC [GCF_028533385.1; DNAzoo.org, Dudchenko et al 2017; Dudchenko et al 2018]. The draft assembly for the jaguar was generated by the DNA Zoo team from short insert-size PCR-free DNA-Seq data using w2rap-contigger (Clavijo et al 2017); see (Dudchenko et al 2018) for details.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Modern technology is empowering our community to ask interesting questions about genes and genomes across the tree of life ( Fig. 1 ) from snow leopards ( Armstrong et al . 2022 ), beaded lizards ( Dyson et al .…”
mentioning
confidence: 99%